Jasmonic acid promotes glutathione assisted degradation of chlorothalonil during tomato growth - Gao-Bo Yu; Ru-Nan Chen; Qiu-Sen Chen; Feng-Qiong Chen; Han-Lin Liu; Chun-Yuan Ren; Yu-Xian Zhang; Feng-Jun Yang; Jin-Peng Wei (Ecotoxicology and Environmental Safety, 2022)
Glutathione (GSH) biosynthesis and regeneration play a significant role in the metabolism of chlorothalonil (CHT) in tomatoes. However, the specific regulatory mechanism of GSH in the degradation of CHT remains uncertain. To address this, we investigate the critical regulatory pathways in the degradation of residual CHT in tomatoes. The results revealed that the detoxification of CHT residue in tomatoes was inhibited by buthionine sulfoximine and oxidized glutathione pretreatment, which increased by 26% and 46.12% compared with control, respectively. Gene silencing of γECS, GS, and GR also compromised the CHT detoxification potential of plants, which could be alleviated by GSH application and decreased the CHT accumulation by 33%, 25%, and 21%, respectively. Notably, it was found that the jasmonic acid (JA) pathway participated in the degradation of CHT regulated by GSH. CHT residues reduced by 28% after application of JA. JA played a role downstream of the glutathione pathway by promoting the degradation of CHT residue in tomatoes via nitric oxide signaling and improving the gene expression of antioxidant and detoxification-related enzymes. This study unveiled a crucial regulatory mechanism of GSH via the JA pathway in CHT degradation in tomatoes and offered new insights for understanding residual pesticide degradation.